Long-term evaluation of spontaneous release of epiretinal membrane and its possible pathogenesis - Kida T (Dove Medical Press, 2017)
Teruyo Kida,1 Seita Morishita,2 Masanori Fukumoto,1 Takaki Sato,1 Hidehiro Oku,1 Tsunehiko Ikeda1 1Department of Ophthalmology, Osaka Medical College, Takatsuki, 2Department of Ophthalmology, Osaka Kaisei Hospital, Osaka, Japan Purpose: To investigate the characteristics in spontaneous release of epiretinal membrane (ERM) during watchful waiting and to introduce a possible mechanism of pathogenesis as a photo essay.Methods: Records from all patients with ERM were obtained from Osaka Medical College Hospital from January 2001 to October 2012. Visual acuity (VA), fundus photo, and optical coherence tomography (OCT) were reviewed using the medical records. For statistical analysis, VA measured with a Landolt chart was converted to the logarithm of the minimum angle of resolution (logMAR). To investigate the pathogenesis of ERM, tryptase activity in vitreous, which plays a role in tissue fibrosis and remodeling, was measured in patients that underwent a vitrectomy for ERM, macular hole, and proliferative diabetic retinopathy (PDR).Results: ERM was observed in 604 patients and spontaneous release of the ERM was observed in 13 patients with 14 eyes (four males and nine females, aged 33–78 years). Among the 14 eyes, mean VA did not change significantly through the release of the ERMs (0.17±0.18 before and 0.24±0.40 after release, P=0.544). Nine eyes showed posterior vitreous detachment or vitreomacular traction on OCT images and five eyes did not. ERM was released in five eyes with no accompanying vitreous traction by OCT during watchful waiting and seems to have peeled off by itself by contracting and rolling from the inferior side. Three eyes with deteriorated VA underwent vitrectomy due to macular hole or pseudomacular hole. Vitreal tryptase activity was significantly higher in patients with ERM compared to those with PDR (P<0.05).Conclusion: Fundus photos of ERM auto-peeling were taken during long-term follow-up. Spontaneous release of ERM is possibly involved in vitreous traction or membrane contraction. In addition, tryptase may be involved in the development and contraction of ERM. Keywords: epiretinal membrane, auto-peeling, contraction, pathogenesis, tryptase, internal limiting membrane